Direct calibration using atmospheric particles and performance evaluation of Particle Size Magnifier (PSM) 2.0 for sub-10 nm particle measurements - Y. Liu; Y. Liu; A. Yli-Kujala; F. Schmidt-Ott; S. Holm; L. Ahonen; T. Chan; J. Enroth; J. Vanhanen; R. Cai; T. Petäjä; M. Kulmala; et al. (Atmospheric Measurement Techniques)
The Particle Size Magnifier is widely used for measuring nano-sized particles. Here we calibrated the newly developed Particle Size Magnifier version 2.0 (PSM 2.0). We used 1–10 nm particles with different compositions, including metal particles, organic particles generated in the laboratory, and atmospheric particles collected in Helsinki and Hyytiälä. A noticeable difference among the calibration curves was observed. Atmospheric particles from Hyytiälä required higher diethylene glycol (DEG) supersaturation to be activated compared to metal particles (standard calibration particles) and other types of particles. This suggests that chemical composition differences introduce measurement uncertainties and highlights the importance of in situ calibration. The size resolution of PSM 2.0 was characterized using metal particles. The maximum size resolution was observed at 2–3 nm. PSM 2.0 was then operated in Hyytiälä for ambient particle measurements in parallel with a Half Mini differential mobility particle sizer (DMPS). During new particle formation (NPF) events, comparable total particle concentrations were observed between the Half Mini DMPS and PSM 2.0 based on Hyytiälä atmospheric particle calibration. Meanwhile, applying the calibration with metal particles to atmospheric measurements caused an overestimation of 3–10 nm particles. In terms of the particle size distributions, similar patterns were observed between the DMPS and PSM when using the calibration of Hyytiälä atmospheric particles. In summary, PSM 2.0 is a powerful instrument for measuring sub-10 nm particles and can achieve more precise particle size distribution measurements with proper calibration.